Quantum control of molecular fragmentation in strong laser field - Zohrabi, Mohammad (Kansas State University, 2014)
Present advances in laser technology allow the production of ultrashort (≲5 fs, approaching single cycle at 800 nm), intense tabletop laser pulses. At these high intensities laser-matter interactions cannot be described with perturbation theory since multiphoton processes are involved. This is in contrast to photodissociation by the absorption of a single photon, which is well described by perturbation theory. For example, at high intensities (≳5×10[superscript]13 W/cm[superscript]2) the fragmentation of molecular hydrogen ions has been observed via the absorption of three or more photons. In another example, an intriguing dissociation mechanism has been observed where molecular hydrogen ions seem to fragment by apparently absorbing no photons. This is actually a two photon process, photoabsorption followed by stimulated emission, resulting in low energy fragments. We are interested in exploring these kinds of multiphoton processes. Our research group has studied the dynamics and control of fragmentation induced by strong laser fields in a variety of molecular targets. The main goal is to provide a basic understanding of fragmentation mechanisms and possible control schemes of benchmark systems such as H[subscript]2[superscript]+. This knowledge is further extended to more complex systems like the benchmark H[subscript]3[superscript]+ polyatomic and other molecules. In this dissertation, we report research based on two types of experiments. In the first part, we describe laser-induced fragmentation of molecular ion-beam targets. In the latter part, we discuss the formation of highly-excited neutral fragments from hydrogen molecules using ultrashort laser pulses. In carrying out these experiments, we have also extended experimental techniques beyond their previous capabilities. We have performed a few experiments to advance our understanding of laser-induced fragmentation of molecular-ion beams. For instance, we explored vibrationally resolved spectra of O[subscript]2[superscript]+ dissociation using various wavelengths. We observed a vibrational suppression effect in the dissociation spectra due to the small magnitude of the dipole transition moment, which depends on the photon energy --- a phenomenon known as Cooper minima. By changing the laser wavelength, the Cooper minima shift, a fact that was used to identify the dissociation pathways. In another project, we studied the carrier-envelope phase (CEP) dependences of highly-excited fragments from hydrogen molecules. General CEP theory predicts a CEP dependence in the total dissociation yield due to the interference of dissociation pathways differing by an even net number of photons, and our measurements are consistent with this prediction. Moreover, we were able to extract the difference in the net number of photons involved in the interfering pathways by using a Fourier analysis. In terms of our experimental method, we have implemented a pump-probe style technique on a thin molecular ion-beam target and explored the feasibility of such experiments. The results presented in this work should lead to a better understanding of the dynamics and control in molecular fragmentation induced by intense laser fields.
Keywords: Ultrafast laser studies, Molecular-ion beam, Strong field laser studies, Dissociation; Molecular-ion beam; Strong field laser studies; Dissociation; Physics (0605)